Simulation of reinforcement slope using plaxis-2D - Yang, Mingzi (Nanyang Technological University, 2021)
This report will discuss the application of PLAXI-2D for relevant design examples of reinforced slope and case study, involving two design examples by Jewell R A and one case study involving a test set up of a real scale bridge abutment. The slope stability is often defined by the factor of safety (FOS). The report will discuss how relevant is PLAXIS-2D for the two design examples by using the software to calculate FOS of the reinforced slopes. In addition, results such as failure points and potential slip surface generated by the software will be also discussed. Lastly, a case study will be involved, which will be mainly discussing about how different soil material model in PLAXIS-2D will affect the settlement of the reinforced soil slope.